Two new species of Aphidini Latreille, 1802 (Hemiptera: Aphididae) from Turkey - Barjadze, Shalva; Özdemir, Işil; Blackman, Roger (Zootaxa, 2014)
Apterous and alate viviparous females of Protaphis kvavadzei sp. n. on Eryngium campestre (Apiaceae) and Aphis matricariae sp. n. on Matricaria sp. (Asteraceae) from Turkey are described. The new species are differentiated from other aphids colonising these host plants and from species with similar morphology.